Corrosion-resistant splint as well as preparation method and application thereof
The method of activate glass fiber by argon oxygen treatment of carbon fiber and hydrochloric acid, combined with the twin screw extrusion process, corrosion-resistant cable clamps were prepared, which solved the problem of insufficient mechanical properties and corrosion resistance of cable clamps in the prior art, and achieved high strength, Low water absorption and good interface performance.
Patent Information
- Application Number
- CN202411410759.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
AI Technical Summary
Existing cable clamps are difficult to meet actual needs in terms of mechanical properties and corrosion resistance, especially carbon fiber reinforced nylon resin composites have reduced mechanical strength due to high water absorption and poor dispersion, which hinders its wide application.
Carbon fibers are treated with argon-oxygen mixed gas and grafted maleic anhydride, combined with hydrochloric acid to activate glass fibers and load nanotitanium dioxide, and corrosion-resistant clamps are prepared through twin-screw extrusion process to improve carbon fiber dispersion and bonding strength, and reinforced by glass fiber composite Mechanical properties.
It significantly improves the dispersion and bonding strength of carbon fiber in the matrix, reduces water absorption, improves tensile and bending strength and modulus, ensures the lightweight, high strength and waterproofness of the product, and is suitable for high-altitude cable fixation.
Smart Images

Figure CN119242033A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cable clamps, and in particular to a corrosion-resistant clamp and a preparation method and application thereof. Background Art
[0002] At present, cables need to be fixed with cable clamps when they are routed. According to the needs of the working surface, pins or bolts are used to form a protective channel to protect the cables. At present, cable clamps can be divided into two categories according to the material: metal clamps and resin clamps. Resin clamps are widely used because of their light weight and no eddy current.
[0003] Existing cable clamps mainly include: polypropylene resin cable clamps, unsaturated polyester composite cable clamps, but the mechanical properties of both are usually difficult to meet actual needs. Carbon fiber has attracted the attention of many researchers due to its excellent mechanical and thermal properties. In recent years, with the increase in carbon fiber production and the reduction in price, the application of carbon fiber reinforced resin composites has become more and more widespread.
[0004] Polybutylene adipamide (PA46) has high heat resistance and relatively high crystallinity, and excellent hardness retention at high temperatures. If carbon fiber reinforced nylon resin composite materials are used in cable clamps, they should have excellent application prospects.
[0005] However, the amide group ratio in the structure of polybutylene adipamide is relatively high, which makes it highly hygroscopic. This will not only make the cable splints very susceptible to corrosion, but also cause poor dispersion of carbon fibers in it, resulting in reduced mechanical strength, thus hindering its widespread application. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a corrosion-resistant splint and a preparation method and application thereof.
[0007] A corrosion-resistant plywood, the raw materials of which include, by mass, 50-80 parts of polybutylene adipamide, 8-10 parts of toughening agent, 5-10 parts of epoxy resin, 1-2 parts of lubricant, 0.1-0.5 parts of antioxidant, 10-20 parts of carbon fiber, 1-3 parts of maleic anhydride, 10-15 parts of glass fiber, 0.1-1 parts of 3-aminopropyltrimethoxysilane and 5-10 parts of tetrabutyl titanate.
[0008] Preferably, the toughening agent is selected from polyolefin thermoplastic elastomer and / or hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride.
[0009] Preferably, the lubricant is ethylene bisstearamide and / or oxidized polyethylene wax.
[0010] Preferably, the antioxidant is at least one of antioxidant BHT, antioxidant DNP, antioxidant TNP, and antioxidant 1010.
[0011] The method for preparing the corrosion-resistant plywood comprises the following steps: S1. Add glass fiber to hydrochloric acid, ultrasonically treat for 10-30 hours, add anhydrous ethanol, 3-aminopropyltrimethoxysilane and tetrabutyl titanate, continue ultrasonically treating for 1-2 hours, let stand for 5-10 hours, take out, dry to constant weight, then add polybutylene adipamide, toughening agent, epoxy resin, lubricant and antioxidant and stir for 5-10 minutes to obtain a premix; S2, adding carbon fiber to a plasma reaction chamber, introducing a mixed gas with a gas pressure of 15-18 Pa and a gas flow rate of 2-2.8 L / min, wherein the mixed gas includes argon and oxygen, and discharging for 50-150 s at a discharge power of 120-150 W, adding to xylene, adding maleic anhydride thereto, stirring at 150-200 ° C for 10-30 min, filtering, washing, and vacuum drying to obtain activated carbon fiber; S3. Add the premix from the main feed port of the twin-screw extruder, add the activated carbon fiber from the side feed port, and after melt extrusion, cooling, pelletizing, drying, feed into the mold, process and shape at 270-300℃, and demold after cooling.
[0012] Preferably, in S1, the ultrasonic frequency is 5-15 kHz, and the ultrasonic temperature is 60-80°C.
[0013] Preferably, in S1, the drying temperature is 100-120°C.
[0014] Preferably, in S2, the flow ratio of argon to oxygen is 10:1-2.
[0015] Preferably, in S2, the temperature of the twin-screw extruder is set to 290-320°C, the head temperature is set to 290-300°C, and the screw speed is set to 300-500r / min. The above-mentioned corrosion-resistant plywood is used in power equipment.
[0016] Beneficial effects: The present invention uses argon-oxygen mixed gas to treat carbon fiber, activates the surface of carbon fiber, and then grafts maleic anhydride, which is added from the side feeding port, can react better with the epoxy resin in the premix, and further cooperate with PA46 to effectively improve the interface performance of the product, so that the carbon fiber not only has good dispersion between the matrix, but also has high bonding strength and small gaps.
[0017] The invention uses hydrochloric acid to activate the glass fiber and then combines oleophilic nano titanium dioxide on the surface of the glass fiber. The nano titanium dioxide has high loading strength on the surface of the glass fiber and is firmly fixed. The product not only has excellent compatibility with PA46, but also can be grafted with the terminal amino group of PA46, effectively reducing the water absorption rate of PA46 while having high mechanical strength.
[0018] The present invention adopts a compound of glass fiber and carbon fiber, and adds them into the system respectively for effective filling and combination. The two fibers are tightly combined with the nylon matrix, have high tensile strength, good stability, especially excellent bending strength and tensile modulus; at the same time, stress is effectively transferred between the fibers to achieve the purpose of synergistic enhancement.
[0019] Through experiments, it was found that although the tensile strength can be effectively improved without activation treatment of the carbon fiber, the tensile modulus is significantly reduced. The present invention activates the carbon fiber, which not only significantly increases the tensile modulus of the product, but also has excellent bending strength and bending modulus. This is because the carbon fiber and the matrix are organically combined, and the mutual bonding strength is high, and the system gap is small, which can significantly improve the strength of the product on the basis of achieving lightweight.
[0020] The surface-treated composite fiber of the present invention is well dispersed in the matrix and forms a good interface bond with the matrix. The product has the excellent performance of high rigidity and good waterproofness. The operation is simple, and the formed splint has the characteristics of good performance uniformity and excellent corrosion resistance. The present invention can ensure the positioning of the cable, effectively avoid cable damage, is suitable for the fixation of high-altitude cables, and has reliable performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a comparison chart of the water absorption rates of the corrosion-resistant plywood obtained in Example 5, Comparative Examples 1-2, and pure PA46.
[0022] Figure 2 It is a comparison chart of the tensile strength and tensile modulus of the corrosion-resistant plywood obtained in Example 5 and Comparative Examples 1-2.
[0023] Figure 3 It is a comparison chart of the bending strength and bending modulus of the corrosion-resistant plywood obtained in Example 5 and Comparative Examples 1-2.
[0024] Figure 4 This is a comparison chart of the tensile strength retention rate, tensile modulus retention rate, flexural strength retention rate and flexural modulus retention rate of the corrosion-resistant plywood obtained in Example 5 and Comparative Examples 1-2 after being soaked in water. DETAILED DESCRIPTION
[0025] The present invention will be further explained below in conjunction with specific embodiments.
[0026] The glass fiber used below is short chopped alkali-free glass fiber with a diameter of 9 μm and a length of 3 mm, purchased from Hangzhou Gaomou Composite Materials Co., Ltd. The carbon fiber used below has a length of 2 mm, a diameter of 7 μm, and a tensile strength of 4900 MPa, purchased from Cangzhou Zhongmou New Materials Technology Co., Ltd.
[0027] The polyolefin thermoplastic elastomer used below was purchased from Ningbo Yimou New Materials Co., Ltd., and the brand is ExxonMobil 6202FL. The hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride used below is FG1901 in the Kraton FG series of the United States, with a styrene content of 30% and a maleic anhydride grafting rate of 1.5%.
[0028] The water absorption rate of the polybutylene adipamide used below was 4.82% after sampling and testing upon storage (according to GB / T 1034-2008 "Determination of Water Absorption of Plastics"); it should be dried at 110°C for 10 hours before use.
[0029] Example 1 A corrosion-resistant plywood, whose raw materials include: 50kg of polybutylene adipamide, 8kg of polyolefin thermoplastic elastomer, 5kg of epoxy resin E51, 1kg of ethylene bisstearamide, 1kg of antioxidant BHT, 10kg of carbon fiber, 1kg of maleic anhydride, 10kg of glass fiber, 0.1kg of 3-aminopropyltrimethoxysilane, and 5kg of tetrabutyl titanate.
[0030] The method for preparing the corrosion-resistant plywood comprises the following steps: S1. Add glass fiber to 40 kg of 4 mol / L hydrochloric acid, perform ultrasonic treatment for 10 h, the ultrasonic frequency is 5 kHz, the ultrasonic temperature is 60 ° C, add 20 kg of anhydrous ethanol, 3-aminopropyltrimethoxysilane, and tetrabutyl titanate thereto, continue ultrasonic treatment for 1 h, let stand for 5 h, take out, dry in an oven at 100 ° C to constant weight, add to a mixer, add polybutylene adipamide, polyolefin thermoplastic elastomer, epoxy resin E51, ethylene bis stearamide, and antioxidant BHT, stir at a speed of 1000 r / min for 5 min to obtain a premix; S2, adding carbon fiber to a plasma reaction chamber, introducing a mixed gas with a gas pressure of 15Pa and a gas flow rate of 2L / min, wherein the mixed gas includes argon and oxygen, wherein the flow ratio of argon to oxygen is 10:1, discharging at a power of 120W for 50s, adding to 40kg of xylene, adding maleic anhydride thereto, stirring at a temperature of 150°C for 10min, filtering, washing, and vacuum drying to obtain activated carbon fiber; S3. Set the temperature of the twin-screw extruder to 290°C, the head temperature to 290°C, and the screw speed to 300r / min. Add the premix from the main feed port of the twin-screw extruder, and add the activated carbon fiber from the side feed port. After melt extrusion, cooling, pelletizing, and drying, obtain the blank. Evenly apply the release agent to the inner surface of the mold, preheat the mold, add the blank into it, process and shape it at a temperature of 270°C, and demold it after cooling.
[0031] Example 2 A corrosion-resistant plywood, whose raw materials include: 80kg of polybutylene adipamide, 10kg of polyolefin thermoplastic elastomer, 10kg of epoxy resin E51, 2kg of oxidized polyethylene wax, 0.5kg of antioxidant DNP, 20kg of carbon fiber, 3kg of maleic anhydride, 15kg of glass fiber, 1kg of 3-aminopropyltrimethoxysilane, and 10kg of tetrabutyl titanate.
[0032] The method for preparing the corrosion-resistant plywood comprises the following steps: S1. Add glass fiber to 60 kg of 6 mol / L hydrochloric acid, perform ultrasonic treatment for 30 h, the ultrasonic frequency is 15 kHz, the ultrasonic temperature is 80°C, add 40 kg of anhydrous ethanol, 3-aminopropyltrimethoxysilane, and tetrabutyl titanate thereto, continue ultrasonic treatment for 2 h, let stand for 10 h, take out, dry in an oven at 120°C to constant weight, add to a mixer, add polybutylene adipamide, polyolefin thermoplastic elastomer, epoxy resin E51, oxidized polyethylene wax, and antioxidant DNP, stir at a speed of 2000 r / min for 10 min to obtain a premix; S2, adding carbon fiber to a plasma reaction chamber, introducing a mixed gas with a gas pressure of 18Pa and a gas flow rate of 2.8L / min, wherein the mixed gas includes argon and oxygen, wherein the flow ratio of argon to oxygen is 10:2, discharging at a power of 150W for 150s, adding to 80kg of xylene, adding maleic anhydride thereto, stirring at a temperature of 200°C for 30min, filtering, washing, and vacuum drying to obtain activated carbon fiber; S3. Set the temperature of the twin-screw extruder to 320°C, the head temperature to 300°C, and the screw speed to 500r / min. Add the premix from the main feed port of the twin-screw extruder and add the activated carbon fiber from the side feed port. After melt extrusion, cooling, pelletizing, and drying, obtain the blank. Evenly apply the release agent to the inner surface of the mold, preheat the mold, add the blank thereto, process and shape it at a temperature of 300°C, and demold it after cooling.
[0033] Example 3 A corrosion-resistant plywood, whose raw materials include: 60kg of polybutylene adipamide, 9.5kg of hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride, 6kg of epoxy resin E51, 1.7kg of ethylene bisstearamide, 0.2kg of antioxidant TNP, 18kg of carbon fiber, 1.5kg of maleic anhydride, 14kg of glass fiber, 0.3kg of 3-aminopropyltrimethoxysilane, and 9kg of tetrabutyl titanate.
[0034] The method for preparing the corrosion-resistant plywood comprises the following steps: S1. Add glass fiber to 45 kg of 5.5 mol / L hydrochloric acid, perform ultrasonic treatment for 12 h, the ultrasonic frequency is 12 kHz, the ultrasonic temperature is 65 ° C, add 35 kg of anhydrous ethanol, 3-aminopropyltrimethoxysilane, and tetrabutyl titanate thereto, continue ultrasonic treatment for 80 min, let stand for 9 h, take out, dry in an oven at 105 ° C to constant weight, add to a mixer, add polybutylene adipamide, hydrogenated styrene-butadiene-styrene triblock copolymer grafted maleic anhydride, epoxy resin E51, ethylene bisstearamide, and antioxidant TNP, stir at a speed of 1200 r / min for 9 min to obtain a premix; S2, adding carbon fiber to a plasma reaction chamber, introducing a mixed gas with a gas pressure of 16Pa and a gas flow rate of 2.6L / min, wherein the mixed gas includes argon and oxygen, wherein the flow ratio of argon to oxygen is 10:1.2, discharging at a power of 140W for 80s, adding to 70kg of xylene, adding maleic anhydride thereto, stirring at a temperature of 160°C for 25min, filtering, washing, and vacuum drying to obtain activated carbon fiber; S3. Set the temperature of the twin-screw extruder to 300°C, the head temperature to 298°C, and the screw speed to 350r / min. Add the premix from the main feed port of the twin-screw extruder and add the activated carbon fiber from the side feed port. After melt extrusion, cooling, pelletizing, and drying, obtain the blank. Evenly apply the release agent to the inner surface of the mold, preheat the mold, add the blank into it, process and shape it at a temperature of 290°C, and demold it after cooling.
[0035] Example 4 A corrosion-resistant plywood, whose raw materials include: 70kg of polybutylene adipamide, 8.5kg of hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride, 8kg of epoxy resin E51, 1.3kg of oxidized polyethylene wax, 0.4kg of antioxidant 1010, 12kg of carbon fiber, 2.5kg of maleic anhydride, 12kg of glass fiber, 0.7kg of 3-aminopropyltrimethoxysilane, and 7kg of tetrabutyl titanate.
[0036] The method for preparing the corrosion-resistant plywood comprises the following steps: S1. Add glass fiber to 55 kg of 4.5 mol / L hydrochloric acid, and perform ultrasonic treatment for 24 h at a frequency of 6 kHz and a temperature of 75°C. Add 25 kg of anhydrous ethanol, 3-aminopropyltrimethoxysilane and tetrabutyl titanate and continue the ultrasonic treatment for 100 min. Let stand for 7 h, take out, dry in an oven at 115°C to constant weight, add to a mixer, add polybutylene adipamide, hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride, epoxy resin E51, oxidized polyethylene wax and antioxidant 1010, and stir at a speed of 1800 r / min for 7 min to obtain a premix. S2, adding carbon fiber to a plasma reaction chamber, introducing a mixed gas with a gas pressure of 17Pa and a gas flow rate of 2.2L / min, wherein the mixed gas includes argon and oxygen, wherein the flow ratio of argon to oxygen is 10:1.8, discharging at a power of 130W for 120s, adding to 50kg of xylene, adding maleic anhydride thereto, stirring at a temperature of 180°C for 15min, filtering, washing, and vacuum drying to obtain activated carbon fiber; S3. Set the temperature of the twin-screw extruder to 310°C, the head temperature to 292°C, and the screw speed to 450r / min. Add the premix from the main feed port of the twin-screw extruder and add the activated carbon fiber from the side feed port. After melt extrusion, cooling, pelletizing, and drying, obtain the blank. Evenly apply the release agent to the inner surface of the mold, preheat the mold, add the blank into it, process and shape it at a temperature of 280°C, and demold it after cooling.
[0037] Example 5 A corrosion-resistant plywood, whose raw materials include: 65kg of polybutylene adipamide, 9kg of hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride, 7kg of epoxy resin E51, 1.5kg of ethylene bisstearamide, 0.3kg of antioxidant BHT, 15kg of carbon fiber, 2kg of maleic anhydride, 13kg of glass fiber, 0.5kg of 3-aminopropyltrimethoxysilane, and 8kg of tetrabutyl titanate.
[0038] The method for preparing the corrosion-resistant plywood comprises the following steps: S1. Add glass fiber to 50 kg of 5 mol / L hydrochloric acid, perform ultrasonic treatment for 18 h, the ultrasonic frequency is 9 kHz, the ultrasonic temperature is 70 ° C, add 30 kg of anhydrous ethanol, 3-aminopropyltrimethoxysilane, and tetrabutyl titanate thereto, continue ultrasonic treatment for 90 min, let stand for 8 h, take out, dry in an oven at 110 ° C to constant weight, add to a mixer, add polybutylene adipamide, hydrogenated styrene-butadiene-styrene triblock copolymer grafted maleic anhydride, epoxy resin E51, ethylene bisstearamide, and antioxidant BHT, stir at a speed of 1500 r / min for 8 min to obtain a premix; S2, adding carbon fiber to a plasma reaction chamber, introducing a mixed gas with a gas pressure of 16.5 Pa and a gas flow rate of 2.4 L / min, wherein the mixed gas includes argon and oxygen, wherein the flow ratio of argon to oxygen is 10:1.5, discharging at a power of 150 W for 100 s, adding to 60 kg of xylene, adding maleic anhydride thereto, stirring at a temperature of 170 ° C for 20 min, filtering, washing, and vacuum drying to obtain activated carbon fiber; S3. Set the temperature of the twin-screw extruder to 305°C, the head temperature to 295°C, and the screw speed to 400r / min. Add the premix from the main feed port of the twin-screw extruder and add the activated carbon fiber from the side feed port. After melt extrusion, cooling, pelletizing, and drying, obtain the blank. Evenly apply the release agent to the inner surface of the mold, preheat the mold, add the blank thereto, process and shape it at a temperature of 285°C, and demold it after cooling.
[0039] Comparative Example 1 A corrosion-resistant plywood, whose raw materials include: 65kg of polybutylene adipamide, 9kg of hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride, 7kg of epoxy resin E51, 1.5kg of ethylene bisstearamide, 0.3kg of antioxidant BHT, 15kg of carbon fiber, 13kg of glass fiber, 0.5kg of 3-aminopropyltrimethoxysilane, and 8kg of tetrabutyl titanate.
[0040] The method for preparing the corrosion-resistant plywood comprises the following steps: S1. Add glass fiber to 50 kg of 5 mol / L hydrochloric acid, perform ultrasonic treatment for 18 h, the ultrasonic frequency is 9 kHz, the ultrasonic temperature is 70 ° C, add 30 kg of anhydrous ethanol, 3-aminopropyltrimethoxysilane, and tetrabutyl titanate thereto, continue ultrasonic treatment for 90 min, let stand for 8 h, take out, dry in an oven at 110 ° C to constant weight, add to a mixer, add polybutylene adipamide, hydrogenated styrene-butadiene-styrene triblock copolymer grafted maleic anhydride, epoxy resin E51, ethylene bisstearamide, and antioxidant BHT, stir at a speed of 1500 r / min for 8 min to obtain a premix; S2. Set the temperature of the twin-screw extruder to 305°C, the head temperature to 295°C, and the screw speed to 400r / min. Add the premix from the main feed port of the twin-screw extruder, and add the carbon fiber from the side feed port. After melt extrusion, cooling, pelletizing, and drying, obtain the blank. Evenly apply the release agent to the inner surface of the mold, preheat the mold, add the blank thereto, process and shape it at a temperature of 285°C, and demold it after cooling.
[0041] Comparative Example 2 A corrosion-resistant plywood, whose raw materials include: 65kg of polybutylene adipamide, 9kg of hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride, 7kg of epoxy resin E51, 1.5kg of ethylene bisstearic acid amide, 0.3kg of antioxidant BHT, 15kg of carbon fiber, 2kg of maleic anhydride and 13kg of glass fiber.
[0042] The method for preparing the corrosion-resistant plywood comprises the following steps: S1, adding glass fiber into a mixer, adding polybutylene adipamide, hydrogenated styrene-butadiene-styrene triblock copolymer grafted maleic anhydride, epoxy resin E51, ethylene bis stearamide, and antioxidant BHT, and stirring at a speed of 1500 r / min for 8 minutes to obtain a premix; S2, adding carbon fiber to a plasma reaction chamber, introducing a mixed gas with a gas pressure of 16.5 Pa and a gas flow rate of 2.4 L / min, wherein the mixed gas includes argon and oxygen, wherein the flow ratio of argon to oxygen is 10:1.5, discharging at a power of 150 W for 100 s, adding to 60 kg of xylene, adding maleic anhydride thereto, stirring at a temperature of 170 ° C for 20 min, filtering, washing, and vacuum drying to obtain activated carbon fiber; S3. Set the temperature of the twin-screw extruder to 305°C, the head temperature to 295°C, and the screw speed to 400r / min. Add the premix from the main feed port of the twin-screw extruder and add the activated carbon fiber from the side feed port. After melt extrusion, cooling, pelletizing, and drying, obtain the blank. Evenly apply the release agent to the inner surface of the mold, preheat the mold, add the blank thereto, process and shape it at a temperature of 285°C, and demold it after cooling.
[0043] The corrosion-resistant plywood obtained in Example 5 and Comparative Examples 1-2 was sampled, and the water absorption rate of each group of samples was measured with reference to GB / T 1462-2005 "Test method for water absorption of fiber reinforced plastics".
[0044] like Figure 1 As shown, relative to PA46, the water absorption rates of the corrosion-resistant plywood obtained in Example 5 and Comparative Examples 1-2 are greatly reduced; and the water absorption rate of the corrosion-resistant plywood obtained in Example 5 is the lowest, which is better than Comparative Examples 1-2 (P < 0.05).
[0045] The corrosion-resistant plywood obtained in Example 5 and Comparative Examples 1-2 was sampled, and the tensile strength and tensile modulus of each group of samples were measured with reference to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics".
[0046] like Figure 2 As shown, the tensile strength and tensile modulus of the corrosion-resistant plywood obtained in Example 5 are both the highest, and are better than those in Comparative Examples 1-2 (P < 0.05); and relative to Example 5, the tensile strength of the corrosion-resistant plywood obtained in Comparative Example 1 only decreases by 10.63%, but the tensile modulus decreases by 68.01%.
[0047] The corrosion-resistant plywood obtained in Example 5 and Comparative Examples 1-2 was sampled, and the bending strength and bending modulus of each group of samples were measured with reference to GB / T9341-2008 "Determination of Flexural Properties of Plastics".
[0048] like Figure 3 As shown, the bending strength and bending modulus of the corrosion-resistant splint obtained in Example 5 are both the highest, and are better than those in Comparative Examples 1-2 (P < 0.05).
[0049] The corrosion-resistant plywood obtained in Example 5 and Comparative Examples 1-2 was sampled, immersed in deionized water at 23° C. for 24 hours, taken out, and tested for tensile strength, tensile modulus, flexural strength and flexural modulus, and the retention rate of each property was calculated.
[0050] like Figure 4 As shown, the corrosion-resistant plywood obtained in Example 5 has the highest retention rates of various properties.
[0051] The applicant believes that this is because the present invention uses argon oxygen mixed gas to treat carbon fiber, activates the surface of carbon fiber, and then grafts maleic anhydride, which is added from the side feed port, can react better with epoxy resin in the premix, and further cooperate with polybutylene adipamide (PA46), effectively improving the interface performance of the product, so that the carbon fiber not only has good dispersion between the matrix, but also has high bonding strength and small gap. At the same time, the present invention uses hydrochloric acid to activate the glass fiber, and then combines oleophilic nano titanium dioxide on its surface. The nano titanium dioxide has high load strength on the surface of the glass fiber and is firmly fixed. The product not only has excellent compatibility with PA46, but also can be grafted with the terminal amino group of PA46. While effectively reducing the water absorption rate of PA46, it has high mechanical strength. The present invention uses glass fiber and carbon fiber compound, and adds them to the system for effective filling and bonding respectively. The two fibers are tightly bonded to the nylon matrix, have high tensile strength, good stability, especially excellent bending strength and tensile modulus; at the same time, the fibers effectively transmit stress to achieve the purpose of synergistic enhancement.
[0052] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A corrosion-resistant plywood, characterized in that: The raw materials include, by mass, 50-80 parts of polybutylene adipamide, 8-10 parts of toughening agent, 5-10 parts of epoxy resin, 1-2 parts of lubricant, 0.1-0.5 parts of antioxidant, 10-20 parts of carbon fiber, 1-3 parts of maleic anhydride, 10-15 parts of glass fiber, 0.1-1 parts of 3-aminopropyltrimethoxysilane and 5-10 parts of tetrabutyl titanate.
2. The corrosion-resistant plywood according to claim 1, characterized in that: The toughening agent is polyolefin thermoplastic elastomer or / and hydrogenated styrene-butadiene-styrene triblock copolymer grafted with maleic anhydride.
3. The corrosion-resistant plywood according to claim 1, characterized in that: The lubricant is ethylene bis stearamide and / or oxidized polyethylene wax.
4. The corrosion-resistant plywood according to claim 1, characterized in that: The antioxidant is at least one of antioxidant BHT, antioxidant DNP, antioxidant TNP, and antioxidant 1010.
5. A method for preparing the corrosion-resistant plywood according to any one of claims 1 to 4, characterized in that: The steps include: S1. Add glass fiber to hydrochloric acid, ultrasonically treat for 10-30 hours, add anhydrous ethanol, 3-aminopropyltrimethoxysilane and tetrabutyl titanate, continue ultrasonically treating for 1-2 hours, let stand for 5-10 hours, take out, dry to constant weight, then add polybutylene adipamide, toughening agent, epoxy resin, lubricant and antioxidant and stir for 5-10 minutes to obtain a premix; S2, adding carbon fiber to a plasma reaction chamber, introducing a mixed gas with a gas pressure of 15-18 Pa and a gas flow rate of 2-2.8 L / min, wherein the mixed gas includes argon and oxygen, and discharging for 50-150 s at a discharge power of 120-150 W, adding to xylene, adding maleic anhydride thereto, stirring at 150-200 ° C for 10-30 min, filtering, washing, and vacuum drying to obtain activated carbon fiber; S3. Add the premix from the main feed port of the twin-screw extruder, add the activated carbon fiber from the side feed port, and after melt extrusion, cooling, pelletizing, drying, feed into the mold, process and shape at 270-300℃, and demold after cooling.
6. The method for preparing the corrosion-resistant plywood according to claim 5, characterized in that: In S1, the ultrasonic frequency is 5-15kHz and the ultrasonic temperature is 60-80°C.
7. The method for preparing the corrosion-resistant plywood according to claim 5, characterized in that: In S1, the drying temperature is 100-120°C.
8. The method for preparing the corrosion-resistant plywood according to claim 5, characterized in that: In S2, the flow ratio of argon to oxygen is 10:1-2.
9. The method for preparing the corrosion-resistant plywood according to claim 5, characterized in that: In S3, the temperature of the twin-screw extruder is 290-320°C, the head temperature is 290-300°C, and the screw speed is 300-500r / min.
10. Use of the corrosion-resistant plywood according to any one of claims 1 to 4 or the corrosion-resistant plywood prepared by the preparation method according to any one of claims 5 to 9 in power equipment.